Learning from the Highlander experience: Contributions of the post-civil rights period - Tom Heaney; Judy Austermiller; Lee Williams; John Gaventa (Adult Education Research Conference, 1994)
In recent years, Highlander has become widely known among aspiring adult education professionals - celebrated, in fact - a legend all the more remarkable because it is living still. While its early history is often reduced in the curriculum of graduate programs to an array of anecdotes which support the profession's renewed but marginal interest in social purpose, the more recent work of Highlander suggests a vision and potential for adult education as a local response to national and global issues. We've become selectively fascinated with "our" past, perhaps because our present has become so boring, so like schooling. We recognize that Highlander's past is inextricably linked with the great social movements in the 30s, 40s and 50s. But even more fascinating is Highlander's endurance. Actually, there have been many Highlanders, each articulated as its work moved across the South and adapted itself to changing conditions of oppression and an emerging potential for collective action. Only Highlander's principles and commitments have remained the same. In the presentations that follow we will have an opportunity to hear about research growing from Highlander's more recent history - events that have unfolded since the fine and seminal texts of Frank Adams, Aimee Horton, John Glen and others. We will look closely at the contributions which the more contemporary achievements of Highlander have made to the field of adult education - contributions which will engender discussion of the principles of democratic education for social change.